Association of Self-Perception Lifestyle with Overweight/Obesity among People with a Family History of Type 2 Diabetes: A Bibliographic Review - Arias-Morales, Michelle; Perez-Velazquez, Luis Ignacio; Villanueva-Mendez, Edith Fernanda; Flores-Vargas, Gilberto; Gallardo-Luna, Maria de Jesus; Navarro-Olivos, Efrain; Arce-Padilla, Ligia Gricelda; Padilla-Raygoza, Nicolas (Recent Updates in Disease and Health Research Vol. 8, 2024)
Lifestyle can be defined as the set of habits and behaviors that people adopt in their daily lives, characterized by being susceptible to modification. Its importance it’s in the appearance or not of non-communicable diseases, including diabetes, cardiovascular diseases, and obesity, the last being defined as the excessive accumulation of fat in tissues, capable of acting as a risk factor for the development of diseases of the same classification. In this work, a literature review of the topic will be conducted, focusing on studies that have analyzed the association between personal perception of lifestyle and the development of obesity/overweight in populations predisposed to diabetes due to hereditary causes. It is important how individuals with obesity/overweight perceive themselves, because is an opportunity area for implementing relevant preventive actions to improve health status and prevent the apparition of diabetes and cardiovascular diseases.